A New Type Of Closed Sets In Terms Of Grills - Mani Parimala, Ibtesam Alshammari , P.M.Sithar Selvam (International Journal of Modern Agriculture, 2020)
In this paper, we introduce and investigate the notions of αω- border, αω-derived, αω-frontier, αω-exterior of a set using the concept of αω- open sets. Further, we shall define the αω(θ)-adherence and αω(θ)- convergence using the concept of grills and study some of their properties.